Comparisons of short‐term efficacy between individual and group cognitive behavioral therapy for primary insomnia. Issue 3 (7th August 2013) - Yamadera, Wataru; Sato, Miki; Harada, Daisuke; Iwashita, Masayuki; Aoki, Ryo; Obuchi, Keita; Ozone, Motohiro; Itoh, Hiroshi; Nakayama, Kazuhiko
Abstract: The purpose of this study was to compare the efficacy of individual and group cognitive behavioral therapy for insomnia (CBT‐I) in outpatients with primary insomnia diagnosed by DSM‐IV‐TR. The participants were 20 individually treated (I‐CBT‐I) and 25 treated in a group therapy format (three to five patients per group) (G‐CBT‐I), which showed no significant difference regarding demographic variables between groups. The same components of CBT‐I stimulus control therapy, sleep restriction therapy, cognitive therapy, and sleep hygiene education were applied on both groups. The short‐term outcome (4 weeks after treatment) was measured by sleep logs, actigraphy, the Pittsburgh Sleep Quality Index (PSQI), and the Dysfunctional Beliefs and Attitudes about Sleep Scale (DBAS), and was compared between I‐CBT‐I and G‐CBT‐I. The results indicated that CBT‐I was effective in improving subjective and objective sleep parameters and subjective sleep evaluations for both individual and group treatment. However, I‐CBT‐I resulted in significantly better improvements over G‐CBT‐I, in (i) objective and subjective sleep onset latency time, (ii) objective sleep efficacy and moving time during sleeping, (iii) overall sleep quality and duration of actual sleep time in PSQI, (iv) consequences of insomnia, control and predictability of sleep, sleep requirement expectation, and sleep‐promoting practices in DBAS. The present study suggested the superiority of I‐CBT‐I over G‐CBT‐I in clinical settings, and further evaluations are necessary.